Pengaruh Fear Of Missing Out (Fomo), Gaya Hidup, Content Marketing Dan Flash Sale Terhadap Pembelian Impulsif Produk Sepatu Aerostreet Di Tiktokshop (Studi Kasus Pada Mahasiswa Kota Malang) - Su’ada, Naimatus; Asiyah, Siti; Rachmadi, Kartika Rose (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the effect of Fear of Missing Out (FOMO), lifestyle, marketing content, and flash sale on the purchase of impulsive aerostreet shoes products in Tiktokshop. The population used in this study is consumers who have purchased impulsively on aerostreet diktiktokshop shoes. The sample of this study was 85 student respondents in Malang with sampling techniques, Purposive Sampling. The results of multiple linear regression analysis show that FOMO, lifestyle, content marketing, and flash sale simultaneously have a significant effect on impulsive purchases. Partially, FOMO has a significant effect on impulsive purchases, lifestyle has a significant effect on impulsive purchases, while content marketing and flash sale show positive positives to impulsive purchases. This research has implications for marketers and business people to understand the factors that encourage impulsive purchases and design effective marketing strategies in Tiktokshop. Keywords: fear of missing out, lifestyle, content marketing, flash sale, impulse purchases, Tiktokshop